Hijras: The 21st Century Untouchables - Sapna Khatri (Washington University Global Studies Law Review, 2017)
Denied the most basic of human rights, this analytical framework aims to prove an overview of the plight of India’s hijras and proposes greater access to health and education for India’s longest lasting social outcasts in an attempt to help them out-caste the nation’s social hierarchy.
Keywords: India; hijras; caste system; social hierarchy; eunuchs; castrated men; transgender; trans; third gender; NALSA v. Union of India; LGBTQ; disenfranchisement